A new genus and three new species of hysteriaceous ascomycetes from the semiarid region of Brazil - de Almeida, Davi Augusto Carneiro; Gusmão, Luís Fernando Pascholati; Miller, Andrew Nicholas (Phytotaxa, 2014)
During an inventory of ascomycetes in the semi-arid region of Brazil, one new genus and three new species of hysteriaceous ascomycetes were found. Maximum likelihood and Bayesian phylogenetic analyses of the nuclear ribosomal 28S large subunit were performed to investigate the placement of the new taxa within the class Dothideomycetes. Anteaglonium brasiliense is described as a new species within the order Pleosporales, and Graphyllium caracolinense is described as a new species nested inside Hysteriales. Morphological and molecular data support Hysterodifractum as a new monotypic genus in the Hysteriaceae. The type species, H. partisporum, is characterized by navicular, carbonaceous, gregarious hysterothecia and pigmented, fusiform ascospores that disarticulate into 16 ovoid or obovoid, septate, part-spores. This is the first report of a hysteriaceous fungus producing part-spores.